Does Male Circumcision Reduce Women's Risk of Sexually Transmitted Infections, Cervical Cancer, and Associated Conditions? - Morris, Brian J.; Hankins, Catherine A.; Banerjee, Joya; Lumbers, Eugenie R.; Mindel, Adrian; Klausner, Jeffrey D.; Krieger, John N. (Frontiers in Public Health, 2019)
Background: Male circumcision (MC) is proven to substantially reduce men’s risk of a number of sexually transmitted infections (STIs). We conducted a detailed systematic review of the scientific literature to determine the relationship between MC and risk of STIs and associated conditions in women. Methods: Database searches by “circumcision women” and “circumcision female” identified 68 relevant articles for inclusion. Examination of bibliographies of these yielded 14 further publications. Each was rated for quality using a conventional rating system. Results: Evaluation of the data from the studies retrieved showed that MC is associated with a reduced risk in women of being infected by oncogenic human papillomavirus (HPV) genotypes and of contracting cervical cancer. Data from randomized controlled trials and other studies has confirmed that partner MC reduces women’s risk not only of oncogenic HPV, but as well Trichomonas vaginalis, bacterial vaginosis and possibly genital ulcer disease. For herpes simplex virus type 2, Chlamydia trachomatis, Treponema pallidum, human immunodeficiency virus and candidiasis, the evidence is mixed. Male partner MC did not reduce risk of gonorrhoea, Mycoplasma genitalium, dysuria or vaginal discharge in women. Conclusion: MC reduces risk of oncogenic HPV genotypes, cervical cancer, Trichomonas vaginalis, bacterial vaginosis and possibly genital ulcer disease in women. The reduction in risk of these STIs and cervical cancer adds to the data supporting global efforts to deploy MC as a health-promoting and life-saving public health measure and supplements other STI prevention strategies.